Strategi Kebijakan Menyongsong Adaptasi Kebiasaan Baru dalam Perspektif Hukum Ekonomi - Asianto Nugroho; Sapto Hermawan (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2020)
This article aims to examine the govermenent policies, including pandemi handling strategies as well as policies to revive national economic growth through a policy strategy that considers opportunities and threats aspects. This paper presents the result of legal researchusing secondary legal material. This article argues that the policy of restoring national economic growth caused by the COVID-19 pandemic can be pursued through several policies based on economic and legal perspective. Several strategies can be taken such as strengthening trade cooperation with the Chinese Government, generating tourism services, strengthening the rural economy, restructuring MSMEs with multiple layers of guarantees, optimizing the role of SOE responsibilities in national development, and strengthening the role of legal political in Indonesia.